Asymmetric Supercapacitors using Manganese Oxide Nanorods and Activated Carbon. Issue 45 (5th December 2022) - Joshi, Ved Prakash; Pathak, Prakash Kumar; Kumar, Nitish; Salunkhe, Rahul R.
Abstract: The utilization of Ionic liquids (ILs) for synthesizing inorganic materials has shown considerable potential in the last decade. The unmatchable advantages, like low vapor pressure, good thermal stability, tunable solubility, and synthesis route flexibility, make them more promising than their aqueous counterparts. This work portrays the use of various ILs for synthesizing asymmetrically oriented α‐MnO2 nanorods. The formation of nanorods was more energetically favorable, and the addition of IL helped increase the material's surface area and conductivity. The enhanced surface and conductivity help in boosting the supercapacitive performance, as the material exhibits 352 F g −1 in 1 M Na2 SO4 electrolyte. The synthesized material and activated carbon were used to assemble an asymmetric supercapacitor device. This device has shown an excellent energy density of 28.5 Wh kg −1 and a power density of 96.5 W kg −1 in 1 M Na2 SO4 electrolyte. Abstract : The asymmetric supercapacitor device (ET‐M//AC) exhibited ultrahigh energy density with stable performance over long cycles.